(3eSGFd SCd YfgG GdbGVi eMeO Hf YHO Gddg Hf MeRgs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3GdChdi ai YHO GdQLd bJd QLdkG NWC , hJYdbJ GdLfGjI HQbHJg , Ke GYJbg eGdcg HYO Pdc s
(3BNQgG (B:s
(3ai cJGH Gddg SHMGfg adg CeKGd cKjQI , aGYde Pdc hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3Gdabg GdESdGejs